Analisis Risiko Keselamatan dan Kesehatan Kerja (K3) pada Aktivitas Servis Kendaraan Menggunakan Metode HIRARC dan FTA di PT. Z - Risvan Arifa Bela; Nissa Syifa Puspani (Fakultas Teknik Universitas Tulang Bawang, 2026)
The growth of vehicle ownership in Indonesia has increased the demand for vehicle maintenance services, which raises the potential for occupational accidents in automotive workshops. PT. Z recorded nine work accidents during 2024, including falling from a vehicle lift and injuries from work tools, reflecting a weak implementation of occupational health and safety (OHS). This study aims to identify hazards, assess risk levels, and determine the root causes of workplace accidents using the Hazard Identification, Risk Assessment and Risk Control (HIRARC) method combined with Fault Tree Analysis (FTA). Data were collected through field observations, interviews, questionnaires, and documentation. The results show that 13 work activities carry various levels of risk, with several identified as high risk. FTA analysis revealed the main causes of accidents: failure to use personal protective equipment (PPE), inadequate training, and uncontrolled work environments. This study concludes that the integration of HIRARC and FTA provides a comprehensive risk analysis and supports the formulation of proactive risk control strategies to improve workplace safety in PT. Z vehicle service environment. Keywords: Fault Tree Analysis, HIRARC, Occupational Safety and Health (OHS), Risk Control, Vehicle Maintenance